2022
DOI: 10.1155/2022/4067812
|View full text |Cite
|
Sign up to set email alerts
|

AGEs/RAGE Promote Osteogenic Differentiation in Rat Bone Marrow-Derived Endothelial Progenitor Cells via MAPK Signaling

Abstract: Systemic vascular impairment is the most common complication of diabetes. Advanced glycation end products (AGEs) can exacerbate diabetes-related vascular damage by affecting the intima and media through a variety of mechanisms. In the study, we demonstrated that AGEs and their membrane receptor RAGE could induce the differentiation of EPCs into osteoblasts under certain circumstances, thereby promoting accelerated atherosclerosis. Differentiation into osteoblasts was confirmed by positive staining for DiI-acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…AGE interacts with RAGE to produce reactive oxygen species that activates nuclear factor kappa-B (NF-kB) and numerous proinflammatory genes of cytokines such as tumor necrosis factor-α (TNF-α), interleukins as IL6, and adhesion molecules ( 47 ). In an animal model, AGE-RAGE induced osteoblast differentiation of EPCs, mediated by p38, MAPK, and JNK signaling, promoting accelerated atherosclerosis ( 48 ). Enrichment of PI3K-AKT and AGE-RAGE signaling pathway for DEGs detected in meta-analysis reinforce the biological significance of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…AGE interacts with RAGE to produce reactive oxygen species that activates nuclear factor kappa-B (NF-kB) and numerous proinflammatory genes of cytokines such as tumor necrosis factor-α (TNF-α), interleukins as IL6, and adhesion molecules ( 47 ). In an animal model, AGE-RAGE induced osteoblast differentiation of EPCs, mediated by p38, MAPK, and JNK signaling, promoting accelerated atherosclerosis ( 48 ). Enrichment of PI3K-AKT and AGE-RAGE signaling pathway for DEGs detected in meta-analysis reinforce the biological significance of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al . [ 48 ] showed that AGEs might bind to RAGE on the membrane of endothelial cells, thereby leading to an increase in differentiation toward osteogenesis.…”
Section: Effect Of Ages On the Differentiation Of Different Types Of ...mentioning
confidence: 99%
“…Wang et al . [ 48 ] showed that AGEs/RAGE promotes osteogenic differentiation of rat bone marrow EPCs through the MAPK signaling pathway. Mitogen-activated protein kinases (MAPK) signaling pathway, a group of mitogen-activated protein kinases that extracellular stimuli can activate, is an important carrier protein that transmits stimuli on the cell surface to the nucleus, including three kinases, including p38 mitogen-activated protein kinases (p38 MAPK), extracellular regulated protein kinases1/2 (ERK1/2), and c-Jun amino-terminal kinase (JNK), which are important components of intracellular signaling pathway transduction involved in a series of cell activities such as regulating cell proliferation, apoptosis, differentiation, and survival as well as functional synchronization between cells [ 117 ].…”
Section: Potential Mechanisms Of Ages Affecting Primary Stem Cell Dif...mentioning
confidence: 99%
“…Hyperglycemia is the most apparent clinical manifestation in diabetes mellitus, and excess free sugars in the body adversely affect many tissues and cells. High levels of extracellular free sugars have a direct inhibitory effect on the cellular activity of, both, osteoblasts and osteocytes ( 54 , 55 ). Osteoblasts exposed to high glucose levels exhibit reduced proliferation capacity, slow extracellular matrix synthesis, and subsequently slow maturation and mineralization.…”
Section: Pathogenesis Of Diabetic Bone Diseasementioning
confidence: 99%